The hybrid work of Marianne North in the context of nineteenth-century visual practice(s) - Gladston, Lynne Helen (2012)
Marianne North was a major figure within the history of nineteenth-century botanical illustration. She produced a substantial body of botanical paintings as the result of extensive travels to many different parts of the world and was responsible for the founding of a major purpose-built gallery containing a representative collection of her work which still stands today in the Royal Botanical Gardens at Kew. Despite North's percieved importance as a botanical painter, relatively little of any critical/analytical substance has been written about her life and work from an art-historical or scientific perspective. North's place within nineteenth-century visual culture is arguably a contested one, despite having been a major contributor to nineteenth-century botanical painting. North's work therefore remains problematic to both botanists and art historians because it does not conform wholly to the established nineteenth century conventions of either scientific-botanical illustration or art. This thesis will explore the uncertain positioning of North's painting through a close analysis of its relationship to nineteenth and twentieth-century visual practices. In light of this analysis, it will be argued that North's painting does not successfully combine artistic and scientific perspectives, as some have argued, but instead presents an unidentifiable mode of visual representation that shifts uncertainly between art and science, thereby deconstructing any categorical distinction between the two.